Зміна показників структури однорічного пагона Quercus rubra в умовах антропогенного навантаження - Бессонова, Валентина Петрівна; Bessonova, Valentina; Криворучко, Анастасія Петрівна; Kryvoruchko, Anastasiia (Дніпровський Національний університет ім. О.Гончара, 2017)
Досліджено вплив інгредієнтів промислових та автомобільних викидів на показники анатомічної структури однорічних пагонів Quercus rubra L. Встановлено, що оболонка потовщена рівномірно як в контрольних, так і в дослідних рослин. Товщина шару корку пагонів рослин Q. rubra, що зростають у придорожньому насадженні, більша, ніж у рослин ботанічного саду на 57,5%. Збільшення її товщини у рослин в умовах забруднення атмосферного повітря має адаптивне значення. З’ясовано, що у пагонів Q. rubra коленхіма пластинчастого типу, клітини якої мають потовщення тангентальних стінок. Ця тканина представлена в контролі в середньому 4-а радіальними рядами клітин, в досліді – 6-а. Клітини коленхіми пагонів контрольного варіанту більші за розмірами. Спостерігається потовщення цієї тканини в пагонів Q. rubra в умовах забруднення середовища в порівнянні з умовно чистою зоною на 26,8%. Клітини паренхіми первинної кори великі та містять хлоропласти. Товщина цього гістологічного елементу по окружності пагона суттєво змінюється як у контрольному, так і в дослідному варіантах, що є наслідком нерівномірного її формування. Серцевина пагона за формою нагадує п’ятикутну зірку, а шари тканин флоеми і ксилеми повторюють її форму і товщина кожної з них на поперечному зрізі пагона в різних його місцях варіює мало, в той час як паренхіма первинної кори в місцях над променями серцевини вужча, а між ними – ширша, за рахунок чого вирівнюється товщина пагона по колу. На ділянках, де паренхіма первинної кори вужча, вона краще розвинена в пагонах дослідних рослин порівняно з контрольними, але там, де її шар товщий, вона більш розвинена у рослин контрольного варіанту. Діаметр первинної кори у пагонах дослідного варіанту в її вужчих частинах становить 120,5% до контролю, а у ширших – 87,5%. В однорічному пагоні Q. rubra твердий луб має вигляд кільця, що розривається ділянками паренхімних клітин. Товщина твердого лубу в пагонах контрольних рослин ширша, ніж в умовах дії на рослини полікомпонентних забруднювачів довкілля на 36,5%. Забруднення довкілля не впливає на формування м’якого лубу у однорічних пагонів Q. rubra. Різниця між товщиною шару цього структурного елемента в умовах контролю і досліду статистично недостовірна. Ширина шару деревини пагонів Q. rubra практично однакова в обох варіантах досліду, хоча відомо, що формування ксилеми деяких видів рослин чутливе до забруднення середовища. Діаметр серцевини вимірювали в двох напрямках: більш вузькому і широкому місцях. Пагони рослин забрудненої ділянки мають значно більш розвинену серцевину в більш вузькому місці в 1,5 раза, в широкому – в 1,4 рази. Розподіл судин у деревині однорічних пагонів Q. rubra на обох дослідних ділянках не має чітко вираженого кільцесудинного типу. На поперечному зрізі судини розташовані відносно рівномірно по ширині всього кільця. Серцевинні промені у пагонах Q. rubra численні та зв'язують кору з серцевиною. Клітини серцевинних променів витягнуті в радіальному напрямку. Деякі промені починаються в товщі деревини на різних відстанях від початку тканини. В умовах полікомпонентного забруднення довкілля в показниках гістологічних елементів пагона Q. rubra відбуваються адаптивні зміни – потовщення фелеми і структурного елемента первинної кори – коленхіми, що сприяє кращому захисту внутрішніх тканин від проникнення забруднювачів. Забруднення довкілля практично не впливає на товщину шару м’якого лубу і деревини в пагонах Q. rubra, що має вагоме значення для збереження показників таких важливих функцій як відтік пластичних речовин у листя, так і поток до них води і мінеральних речовин. Це свідчить про стійкість важливіших функцій пагона Q.rubra до фітотоксикантів антропогенного походження. Air pollution is one of the important problems of large cities. In connection with this, comprehensive study of the mechanisms of the corresponding reactions of introduced tree plants, which are introduced in landscaping, on various environmental factors is required. Therefore, The main aim of this study is to analyze the influence of urbothechnogenic environmental pollution on the anatomical characteristics of Quercus rubra annual shoots. The object of research was 35-year-old plants of Q. rubra, which grew in a non-polluted site (conditionally clean zone) – the botanical garden of DNU (section 1) and in polluted site (roadside planting) (section 2) of the Dnipro City. The components of industrial emissions of the Western, Northeastern and Northwest industrial complexes are also has an effect on plants, depending on the variability of the the wind direction. For anatomical research, the annual shoots were taken at the end of vegetation from the south-eastern side of model trees at a height of 2 m and fixed with 70% alcohol. Cross sections were made at a distance of 1 cm from the beginning of growth. Phloroglucine was used to dye the lignify cells. The influence of industrial and automobile emissions on the structure parameters of Quercus rubra L. shoots was investigated. It was established that the membrane thickens evenly in both control and experimental plants. The cork thickness of Q. rubra shoots, growing in roadside plantation, is higher than in plants of the botanical garden by 57,5%. Increasing its thickness in plants under conditions of atmospheric air pollution has an adaptive value. The Q. rubra shoots have a tabulate type of collenchyma, whose cells have thickening of the tangent walls. This tissue is presented in the control plants on the average the 4th radial row of cells, in the experiment – 6th. The collenchyma cell of the control variant of shoots are larger in size. There is a thickening of this tissue in shoots Q. rubra in conditions of environmental pollution compared with the non-polluted zone by 26,75%. The parenchyma cells of primary cortex are large and contain chloroplasts. The thickness of this histological element on the circumference of the shoot varies considerably both in the control and experimental variants, which is the result of its uneven formation. This is due to the fact that the shoot core in shape resembles a pentagonal star, and the layers of phloem and xylem tissues repeat its shape. The thickness each of them in the cross section of the shoots in its various places varies little, while the parenchyma of the primary cortex above the rays cell is narrower, and between them is broader, as a result the thickness of the shoots is aligned in a circle. In areas, where the parenchyma of the primary cortex is narrower, it is better developed in the shoots of experimental plants than the control ones, but where its layer is thicker, it is more developed in plants of the control variant. The diameter of the primary cortex in the shoots of the experimental variant in its narrower parts is 120,50% to control, and in the broader – 87,57%, which is due to unequal changes in the thickness of the primary cortex parenchyma, possibly with different rates of cell division. In the one-year Q. rubra shoots, the hard bast has the appearance of a circle ruptured by parenchymal cells. A layer of these cells, which membrane have been scleroticed (reaction with floroglycine), strongly and uniformly thickened, in shoots of control plants is wider than in the conditions of influence on plants the polycomponent environmental pollutants by 36,54%. Environment pollution do not affect on formation of a soft bast in Q. rubra annual shoots. The difference between the thickness of the layer of this structural element in conditions of control and experiment is statistically unreliable, which is very important for maintaining the normal functioning of shoots and outflow of plastic substances synthesized in leaves, in other organs. The width of the bark (soft and hard bast) somewhat decreases in shoots of roadside planting trees due to the thinning-out of the hard bast. The thickness of the wood tissue of the Q. rubra shoots is practically the same in both variants of the experiment, although it is known that the formation of xylem of certain species of plants is sensitive to environmental pollution. According to our data, the distribution of vessels in the wood of the Q. rubra annual shoots on both experimental sites has no clearly expressed annular-vessel type, as in some literary sources. On the cross section, the vessels are arranged relatively evenly along the width of the entire ring. The woody parenchyma apotracheal, its location does not depend on the location of vessels. Histochemical reactions have found that a large amount of starch grains and drops of fat are deposited in the core cells and rays cell. The diameter of the core was measured in two directions: in narrower and broader places. Plant shoots of the polluted site have a significantly more developed core in a narrower place in 1,44 times, in broad – 1,56 times. The implementation of the adaptive potential to the technogenic pollution of the environment of the Q.rubra shoots is take place due to thickening of the cork and collenchyma, thereby reducing the possibility of penetration into the internal tissues the industrial and automotive emissions. The thickness of the circle of soft bast and wood in conditions of environmental pollution virtually does not change, which is important for maintaining the indicators as an outflow of plastic substances from the leaves, and the flow of water and minerals to them, that is, the preservation of the functions of these tissues at the control level. Consequently, in the conditions of multicomponent environmental pollution in the parameters of the histological elements of the Q. rubra shoots there are adaptive changes - thickening of the phellem and structural element of the primary cortex – collenchyma, which helps to better protect the internal tissues from the pollutants penetration. Environment pollution practically does not affect the thickness of the layer of soft bast and wood in the Q. rubra shoots. This testifies to the stability of the most important functions of the Q. rubra shoots to phytotoxicants of anthropogenic origin. The components of industrial and automotive emissions have a negative effect on the formation hard bast and core of the Q. rubra shoot, which manifests itself in reducing their thickness.
Changes in the structural indices of annual shoots of Quercus rubra under anthropogenic impact
Keywords: дуб червоний; red oak; урботехногенні умови; anthropogenic impact; характеристики; characteristics; перидерма; periderm; первинна та вторинна кора; primary cortex and bark; деревина; wood tissue